(untitled) (Research, Society and Development, 2022)
The Nursing consultation corroborates health promotion and protection of the population. However, current research shows that this strategy does not always reach its full potential. Thus, this study aimed to identify components that interfere with the practice of Nursing Consultation with the newborn (NB) in Primary Health Care (PHC). To this end, 11 nurses from Family Health Care teams in the municipality of Palmas, Tocantins, Brazil, were interviewed from June to November 2019, and the collected information was submitted to Content Analysis. The results show that the practice of the NB Nursing Consultation is permeated by several challenges, such as difficulties in finding the NB and weaknesses in clinical assessment and in the implementation of the Nursing Process (NP). The components lack of knowledge and technical skills to assess the child, and insipient and unsystematic execution of the steps of data collection and implementation of the NP, negatively, interfere in the practice of Nursing Consultation.